PENGARUH LINGKUNGAN FISIK DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT JAYA HOTEL LESTARI KABUPATEN TANGERANG - Syaeful Azam; Siti Aesah (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to determine the influence of the physical environment and work discipline on employee performance at PT Jaya Hotel Lestari, Tangerang Regency. either partially or simultaneously. The method used in this research is a quantitative method. The sampling technique used was saturated sampling, namely using a sample of 86 respondents. The data analysis technique used is statistical analysis by testing validity tests, reliability tests, classical assumption tests, simple linear tests, multiple linear regression tests, coefficient of determination, hypothesis t tests and hypothesis f tests. Results of research on the physical environment and work discipline on employee performance at PT Jaya Hotel Lestari, Tangerang Regency. Shown by the multiple linear regression equation Y = 2.766 + 0.239 X1 + 0.870 X2. This is proven by the results of simultaneous hypothesis testing which obtained a value of fcount > ftable (119.831 > 3.11) and reinforced by a significance value of <0.05 (0.000 <0.05). The results of the coefficient of determination test for work discipline variables (X1) and physical environment (X2) have an influence of 25.7%. on employee performance at PT Jaya Hotel Lestari Tangerang Regency. Thus, H0 is rejected and H3 is accepted. This means that it is proven that there is a significant simultaneous influence between the physical environment (X1) and work discipline (X2) on employee performance (Y).